RED CELL DISTRIBUTION WIDTH VALUE AS A PREDICTOR OF COPD SEVERITY: ORIGINAL RESEARCH ARTICLE - SHIL, SUMAN; PETHANI, VRUNDA; MALANI, SWATI; dave, amit (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The purpose of the study is to use the red cell distribution width (RDW) value for predicting chronic obstructive pulmonary disease (COPD) severity. Methods: Three hundred COPD patients are included in this retrospective analysis. Oxygen saturation, BODE index variables, and demographic characteristics were noted. All patients’ survival data were analyzed. RDW measurements were evaluated at the time of inclusion. Results: The patients had an average age of 65.2±8.6 years. The patients were divided into the following stages of COPD: stage 1: 14.66%, stage 2: 56.66%, stage 3: 25.6%, and stage 4: 3%. Red cell distribution width was observed differ significantly between stages. The very high RDW was found in the extremely serious stage (p<0.001). The BODE index has a median of 1 (0–3). RDW increased with the BODE index as it increased (p<0.001). The survival percentages for the groups of patients created based on the laboratory upper limit of RDW was 76% for groups with RDW<14.3% and 29% for groups with RDW>14.3%. Conclusion: Our study’s findings suggest that an elevated level of RDW may be linked to increased mortality and that a quick, non-invasive test could be used as an early biomarker to assess the severity of a disease.